The Arts in Curriculum: Aesthetics, Embodiment and Well-Being - Aitken, Avril; Dobson, Margaret; Ezcurra, Maria; Mitchell, Claudia; Strong-Wilson, Teresa (Journal of the Canadian Association for Curriculum Studies, 2018)
This issue invites the reader to join the authors in a quest for the meaning of Arts in Curriculum; it calls on those reading to see, and not merely look. Drawing on the unique perspectives of educators, artists of diverse forms, and curriculum theorists, the issue invites a consideration of how the unique visions and personal experiences expressed in the issue foster thinking about Aesthetics, Embodiment and Well-being and their place in provoking transformation.